2019
DOI: 10.1002/er.4495
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading continuous H2gas recovery from rice straw hydrolysate via fermentation process amended with magnetite nanoparticles

Abstract: Summary Continuous H2 production from alkali‐hydrolyzed rice straw in two mesophillic anaerobic baffled reactors (ABRs) was investigated in parallel. ABR1 was inoculated with thermally pretreated sludge while the sludge in ABR2 was amended with magnetite nanoparticles (MNPs). Both reactors were operated at organic loading rates (OLRs) ranged from 0.8 to 4.8 gCOD/L/day. The addition of MNPs significantly improved the H2 production and yield, ie, maximum H2 yield was 21.4 ± 3.2 and 60.6 ± 5.7 mL/g CODremoved for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Elreedy et al [51] found that decreasing the initial pH value of wastewater from 7.0 to 5.0 enhanced the H 2 productivity 1.44-fold, attaining the maximum value of 79 ± 6 mL. This is mainly due to the positive effect of the acidic pH value of 5.0 on the hydrogenase enzyme activity, as reported by [65][66][67]. Further reduction in pH values less than 5.0 (4-4.5) would inhibit the growth of H 2 producers and reduce the hydrogenase activities.…”
Section: Ph Valuementioning
confidence: 70%
“…Elreedy et al [51] found that decreasing the initial pH value of wastewater from 7.0 to 5.0 enhanced the H 2 productivity 1.44-fold, attaining the maximum value of 79 ± 6 mL. This is mainly due to the positive effect of the acidic pH value of 5.0 on the hydrogenase enzyme activity, as reported by [65][66][67]. Further reduction in pH values less than 5.0 (4-4.5) would inhibit the growth of H 2 producers and reduce the hydrogenase activities.…”
Section: Ph Valuementioning
confidence: 70%
“…Various studies have analyzed the economic feasibility of utilizing NMDs in AD or DF systems, while considering a wide range of costs and benefits. For instance, the addition of 1 and 2 mg/L of Ni-NPs into a manure-fed AD system, led to achieving a net profit of $20.6 and 19.7/m 3 substrate . , Further, during the treatment of biomass mixture (agricultural residues, manure, and glycerol), it was found that adding n-ZVI (0.1 wt %), which led to an increase in biogas productivity by 50%, would be feasible only if the n-ZVI cost was less than $119/kg; , considering that the market price of n-ZVI is $96/kg, a benefit of $23/kg n-ZVI added could be gained. , For DF reactors, it was reported that supplementing n-Fe 3 O 4 could reduce the required payback period from 14.6 years (for unamended reactor) to 10.5 years (for n-Fe 3 O 4 -added reactor), when being operated at OLR of 4.8 g COD/L/d . Interestingly, the same study showed that, at lower OLR (1.1 g COD/L/d), the payback period of the unamended reactor was negative, referring to the impossibility to compensate for the capital cost.…”
Section: Nmds Toxicity Risk Analysismentioning
confidence: 99%
“…Additionally, NMDs were found to be able to provide functional ions that enhance microbial performance and enzymatic activity . Importantly, during DF, hydrogenase enzyme activity is boosted, thanks to a slow but significant iron release from nanosized iron oxides. On the basis of their various merits, NMDs have been extensively employed for enhancing and accelerating the performance of AD and DF treatment systems. , Fruitful efforts have been dedicated in recent review articles for explaining the role played by NMDs in AD and DF. Attention was paid to highlighting NMDs’ advantageous impact. However, full illustration for all possible NMDs–microbes reactions and the interactions between these reactions have not been synthesized yet, and this constitutes the primary objective of this review.…”
Section: Introductionmentioning
confidence: 99%
“…203 The addition of Fe 3 O 4 NPs in AD system was studied and observed a shortened period of time than traditional AD system the time period was reduced from 14.6 to 10.5 years. 222 The economic feasibility of large scale NPs in improved AD systems mostly depend on the cost of NPs. Furthermore, despite the economic feasibility; the utilizing of NPs raises various environmental problems that should be addressed properly.…”
Section: Economic Feasibilitymentioning
confidence: 99%